Karakterisasi Morfologi dan Komponen Hasil Beberapa Calon Hibrida Jagung Manis (Zea mays L. saccharata Sturt) MS - UNSIKA di Dataran Tinggi Wanayasa Purwakarta - Farhan Novfourthino Pradana; Muhammad Syafi’i; Kasdi Pirngadi (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
Morphological characterization is one of the best ways to develop maize varieties, characterization at the morphological level is needed, especially to identify the phenotype and its changes related to the ecotype. The purpose of this study was to determine the morphological character and yield of several prospective sweet corn hybrids (Zea mays L. saccharata Sturt) and to obtain the best line. The research was conducted in the Ambu Garden, Pusakamulya Village, Wanayasa sub District, Purwakarta District, from July 2021 to September 2021. The design used was a non-factorial randomized block design (RBD) with 33 genotypes of prospective hybrids and 3 commercial comparison varieties and 3 replications. The results showed that there was a significant effect of the genotype of the prospective hybrid tested on the morphological characters of plant height, stem diameter, corn cob height, number of corn cob per plant, length of corn cob and diameter of corn cob. The hybrid candidate genotype that showed the highest response to the morphological characterization of plant height was UNSIKA09 with an average value of 176.19 cm, the number of leaves was UNSIKA09 (7.69 strands), the stem diameter character was UNSIKA09 (23.42 dm ), the character of the height of the corn cob position was UNSIKA09 (103.69 cm), while the character of the yield component of the number corn cobs per plant was UNSIKA38 (1.93 cobs), character of the length of the corn cob was UNSIKA01 (21.75 cm), and the diameter character corn cob is UNSIKA03 with an average value of 46.92 dm. There were 25 candidates for hybrid sweet corn that were not significantly different from the comparison varieties, namely UNSIKA01, UNSIKA02, UNSIKA03, UNSIKA09, UNSIKA10, UNSIKA14, UNSIKA15, UNSIKA19, UNSIKA21, UNSIKA22, UNSIKA23, UNSIKA26, UNSIKA27, UNSIKA28, UNSIKAS32, UNSIKAS29, UNSIKA33 , UNSIKA34, UNSIKA36, UNSIKA37, UNSIKA38, and UNSIKA40.